2014
DOI: 10.1111/joor.12148
|View full text |Cite
|
Sign up to set email alerts
|

Posterior scissors‐bite: masticatory jaw movement and muscle activity

Abstract: Scissors-bite is a malocclusion characterised by buccal inclination or buccoversion of the maxillary posterior tooth and/or linguoclination or linguoversion of the mandibular posterior tooth. This type of malocclusion causes reduced contact of the occlusal surfaces and can cause excessive vertical overlapping of the posterior teeth. This case-control study is the first to evaluate both masticatory jaw movement and masseter and temporalis muscle activity in patients with unilateral posterior scissors-bite. Jaw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 38 publications
1
27
0
2
Order By: Relevance
“…Standard 5‐g gummy jelly was specially prepared for this study. The shape of the gummy jelly was similar to that of a truncated cone (5‐g gummy jelly: height, 11 mm; top diameter, 12 mm; base diameter, 22 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Standard 5‐g gummy jelly was specially prepared for this study. The shape of the gummy jelly was similar to that of a truncated cone (5‐g gummy jelly: height, 11 mm; top diameter, 12 mm; base diameter, 22 mm).…”
Section: Methodsmentioning
confidence: 99%
“…This depends on whether the selection of the chewing side is regulated primarily by peripheral asymmetries or is an expression of cerebral dominance, like other functional lateralities. Peripheral factors that have been found to be related to masticatory laterality include asymmetry of several characteristics of occlusion, bite force and masticatory performance, missing posterior teeth and temporomandibular disorders , most of them are interrelated . However, other studies have failed to find a significant association between some of these peripheral factors and the PCS .…”
Section: Introductionmentioning
confidence: 99%
“…Tomonari et al showed that lateral excursion on the scissors bite side was poor due to occlusal interferences in patients with unilateral posterior scissors bite. 19 In the current patient, lateral excursive jaw movements on both sides were irregular for incisor and bilateral condyle movements, and a CR-CO discrepancy was observed at initial presentation. As a result of treatment, satisfactory lateral excursive movements and CR-CO coincidence were achieved, and the maximum open-close movement was maintained.…”
Section: Discussionmentioning
confidence: 55%